(3GdeSGFd hGdCLhHIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3eMeO Hf YjSi Hf CHj GdaVd GdTGaYi s)
(3ChdgG (B:s
(3hSFd QMeg Gddg JYGdi hQVi Yfg Yf ELGQI GdbWGY gd UMjMI Ce HGddg s
(3BNQgG (B:s
(3aEf gDdGA EeG Cf jchfhG eQJOjf hEeGe Cf jchfhG eQJOjf Yf Ojf GdESdGe hGdeQJO dGjchf EdG cGaQkG hGddg CYde s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3CUhd Gdabgs